2019
DOI: 10.1111/bjd.18095
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐cell‐derived complement components C1r and C1s promote growth of cutaneous squamous cell carcinoma

Abstract: Summary Background The incidence of epidermal keratinocyte‐derived cutaneous squamous cell carcinoma (cSCC) is increasing worldwide. Objectives To study the role of the complement classical pathway components C1q, C1r and C1s in the progression of cSCC. Methods The mRNA levels of C1Q subunits and C1R and C1S in cSCC cell lines, normal human epidermal keratinocytes, cSCC tumours in vivo and normal skin were analysed with quantitative real‐time polymerase chain reaction. The production of C1r and C1s was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 59 publications
(114 reference statements)
3
52
0
Order By: Relevance
“…Although C1R is known to regulate the complement pathway of the innate immune system, in this study, we found upregulated CIR expression in HNSCC. This is in concordance with a previous study that correlated the expression of C1R in cutaneous SCC (cSCC) with tumor progression, cell proliferation, and migration [ 67 , 68 ]. Since cSCC lesions frequently develop in the HN region [ 69 ], our data correlate with this finding.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although C1R is known to regulate the complement pathway of the innate immune system, in this study, we found upregulated CIR expression in HNSCC. This is in concordance with a previous study that correlated the expression of C1R in cutaneous SCC (cSCC) with tumor progression, cell proliferation, and migration [ 67 , 68 ]. Since cSCC lesions frequently develop in the HN region [ 69 ], our data correlate with this finding.…”
Section: Discussionsupporting
confidence: 93%
“…Since cSCC lesions frequently develop in the HN region [ 69 ], our data correlate with this finding. Although, the prognostic relevance of C1R has not been studied in cancer; however, it is associated with tumor progression and migration [ 67 , 68 ], hence our data suggest a significant correlation between C1R and shorter RFS. Furthermore, our data implicate the other member of the complement pathway, MASP-2 gene, which is upregulated in oral epithelial cells exposed to WPS.…”
Section: Discussionmentioning
confidence: 69%
“…The authors show that C1r and C1s expression is markedly elevated in invasive sporadic and RDEB‐associated cSCC while their knockdown in cSCC cells inhibited activation of the extracellular signal‐related kinase (ERK) 1/2 and Akt pathway, promoted cSCC apoptosis, and suppressed growth and vascularization of human cSCC xenograft tumours in vivo . Interestingly, RDEB‐SCC sections had the strongest C1r and C1s staining, and the knockdown of C1r and C1s upregulated the production of matrix metalloproteinase‐9 in cSCC cells . Additionally, previous studies have shown that extracellular C1s can cleave and inactivate alarmin high‐mobility group box (HMGB1), hence regulating inflammation and suppressing proinflammatory cytokine production .…”
mentioning
confidence: 98%
“…This issue of the BJD includes an interesting study by Riihila et al ., identifying novel specific biomarkers of invasive sporadic and recessive dystrophic epidermolysis bullosa (RDEB)‐associated cutaneous squamous cell carcinoma (cSCC) . This is a significant finding, as no biomarkers are currently in clinical use to predict cSCC aggressiveness.…”
mentioning
confidence: 99%
See 1 more Smart Citation